Relações entre fracasso escolar e racismo em estudos no campo da psicologia escolar e educacional - Parreão, Yasmin Coelho dos Santos (Universidade Federal do Tocantins, 2023)
The present work emerges from the urgency of guiding racial relations in the process of school failure, since Brazil is a country that has consolidated itself from the crossing of racism. This research aimed to analyze the critical content of school failure and understand how racial relations are intersected in this debate. To investigate this issue, at first, a literature review was carried out, with articles related to the theme through the Scientific Electronic Library Online (SciELO) and the Virtual Health Library - Psicologia Brasil (BVS-Psi). The organization took place in two stages. In the first stage, a bibliographic survey on racism was carried out. The second stage, analysis of the articles in the index databases, looking for similarities and disagreements in the relationship between racism and school failure. To carry out this collection, Boolean indexers “school failure AND racism” were used; “racial inequality OR public school”. After using the inclusion and exclusion criteria, the survey resulted in a total of twenty-eight articles that were read, registered and organized into three categories. The first category brings together texts in which there was no relationship between racism and school failure. The second category groups articles that mention racism, however, without establishing connections with school failure. The third category compiles the texts that bring articulations between racism and school failure. In the texts of the first and second categories, blaming for school failure falls into three dimensions: individual, family and social class. Finally, in the third category, racism is presented as a phenomenon associated with school failure. The Brazilian educational system was built under the influence of racist theories, in this sense, the importance of analyzing school failure through racism is understood. Thus, the results presented deal with the propagation of racial inequality in the Brazilian educational process, culminating in an environment conducive to the production of school failure in the contexts of life and development of black students.